2003
DOI: 10.1084/jem.20021952
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal Membrane Permeabilization Induces Cell Death in a Mitochondrion-dependent Fashion

Abstract: A number of diseases are due to lysosomal destabilization, which results in damaging cell loss. To investigate the mechanisms of lysosomal cell death, we characterized the cytotoxic action of two widely used quinolone antibiotics: ciprofloxacin (CPX) or norfloxacin (NFX). CPX or NFX plus UV light (NFX*) induce lysosomal membrane permeabilization (LMP), as detected by the release of cathepsins from lysosomes. Inhibition of the lysosomal accumulation of CPX or NFX suppresses their capacity to induce LMP and to k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
353
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 412 publications
(368 citation statements)
references
References 47 publications
14
353
0
1
Order By: Relevance
“…Inhibition of cathepsin B can fully rescue cells from tumor necrosis factor-induced apoptosis, demonstrating that the release of cathepsin B to the cytosol can act as a dominant executioner of apoptosis (Foghsgaard et al, 2001). Cathepsin B proteolytic effects include the activation of Bax and Bak, two proapoptotic members of the Bcl-2 family, and subsequent release of cytochrome c through permeabilization of the mitochondrial membrane (Boya et al, 2003;Guicciardi et al, 2000). Cytochrome c is a key activator of the apoptosome, which regulates the mitochondrial caspase activation pathway mediated by caspase-9 (Reed, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of cathepsin B can fully rescue cells from tumor necrosis factor-induced apoptosis, demonstrating that the release of cathepsin B to the cytosol can act as a dominant executioner of apoptosis (Foghsgaard et al, 2001). Cathepsin B proteolytic effects include the activation of Bax and Bak, two proapoptotic members of the Bcl-2 family, and subsequent release of cytochrome c through permeabilization of the mitochondrial membrane (Boya et al, 2003;Guicciardi et al, 2000). Cytochrome c is a key activator of the apoptosome, which regulates the mitochondrial caspase activation pathway mediated by caspase-9 (Reed, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it has been found that lysosomotropic toxins fail to kill cells when the Bax and/or Bak genes are removed from the system or when mitochondrial membranes are sealed by overexpression of Bcl-2 (or the strictly mitochondrion-specific vMIA protein from Cytomegalovirus). 10,11 In such a system, the absence of Bax and/or Bak or the presence of Bcl-2 or vMIA fails to affect the redistribution of cathepsins B and D, yet does block the release of mitochondrial death effectors, including cytochrome c. 10,11 These data point to an obligatory participation of mitochondria in the transmission of lethal signal initially perceived at the lysosomal level. …”
Section: A Lethal Cascade Linking Lysosomes To Mitochondriamentioning
confidence: 99%
“…1 In several other models of LMP-mediated cell death, the inhibition of individual cathepsins (or their knockout) is not sufficient to block the activation of Bax. 10,11 Thus, several cathepsins (and perhaps even other lysosomal hydrolases) may be able to constitute the link between LMP and MMP. Indeed, cysteine cathepsins B, H, L, S, and K have recently been shown to cleave and activate the Bax-activating Bcl-2 family member, Bid, in vitro (Boris Turk, personal communication), and the TNF-induced MMP in hepatocytes depends on the activity of cathepsin B rather than cathepsin D. 5 Such variations in the requirement of individual cathepsins between the diverse apoptosis models may reflect differences in the expression levels of cathepsins themselves or their endogenous cathepsin inhibitors, which are highly cell type dependent.…”
Section: Missing Links Between Lysosomes and Mitochondriamentioning
confidence: 99%
“…41 The probe was added to 2 3 10 5 fresh cells plated on cover slips either treated or not with bafilomycin A1 (5 nM for 2 hr) and incubated at RT for 30 minutes. Cells were then fixed with paraformaldehyde and stained with Hoechst 33245 (GIBCO, Invitrogen) to allow nuclear staining.…”
Section: Fluorescent Microscopymentioning
confidence: 99%